Sheikh Omar bin Badr Al-Mawsili Al-Kurdi (557-622 AH) and His Hadithiya Efforts - Khudhur , Luqman Samad (Zanco Journal of Human Sciences, 2024)
Our Kurdish scholars have played a significant role in various fields and sciences throughout Islamic history, contributing to the advancement of Islamic civilization. Among these scholars is Sheikh Omar bin Badr Al-Mawsili, a prominent figure in the sixth and seventh century AH. His notable contributions lie in the field of the noble sayings of the Prophet, where he dedicated himself to refining, condensing, and collecting authentic hadiths. In pursuit of this goal, he authored an independent book, "Combining the Two Sahihs," amalgamating the hadiths of Imam al-Bukhari and Imam Muslim. The book, organized alphabetically, facilitates easy access for students and scholars. Moreover, Sheikh Omar cautioned against weak and fabricated hadiths attributed to the Messenger of God, writing two books to raise awareness about these fabrications. Beyond his efforts in hadith, he played a crucial role in teaching and explaining Islamic law, earning recognition as one of the leading Hanafi jurists of his time. Sheikh Omar taught in various Hanafi schools across Islamic cities and countries.